2014
DOI: 10.3389/fevo.2014.00011
|View full text |Cite
|
Sign up to set email alerts
|

The impact of incorporating molecular evolutionary model into predictions of phylogenetic signal and noise

Abstract: Phylogenetic inference can be improved by the development and use of better models for inference given the data available, or by gathering more appropriate data given the potential inferences to be made. Numerous studies have demonstrated the crucial importance of selecting a best-fit model to conducting accurate phylogenetic inference given a data set, explicitly revealing how model choice affects the results of phylogenetic inferences. However, the importance of specifying a correct model of evolution for pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 77 publications
1
15
0
Order By: Relevance
“…In the present study, we used five metrics that maximize data quantity (alignment length), attempt to model signal directly (PHYDESIGN; Townsend et al ., ) or use bipartition frequency (mean bootstraps) as a proxy for signal, or minimize topological incongruence amongst the individual gene trees (Robinson–Foulds distances, TC; Salichos & Rokas, ). Studies that have used signal and noise estimation in PHYDESIGN as a guide for gene selection have shown that they perform well in resolving nodes at diverse time scales and taxonomic groups (López‐Giráldez, Moeller & Townsend, ; Su et al ., ). Alternatively, explicit attempts to reduce gene tree incongruence using measures of mean bootstraps or minimizing topological discordance have also shown improvement in phylogeny estimation (Townsend et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…In the present study, we used five metrics that maximize data quantity (alignment length), attempt to model signal directly (PHYDESIGN; Townsend et al ., ) or use bipartition frequency (mean bootstraps) as a proxy for signal, or minimize topological incongruence amongst the individual gene trees (Robinson–Foulds distances, TC; Salichos & Rokas, ). Studies that have used signal and noise estimation in PHYDESIGN as a guide for gene selection have shown that they perform well in resolving nodes at diverse time scales and taxonomic groups (López‐Giráldez, Moeller & Townsend, ; Su et al ., ). Alternatively, explicit attempts to reduce gene tree incongruence using measures of mean bootstraps or minimizing topological discordance have also shown improvement in phylogeny estimation (Townsend et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…We build on the signal and noise framework of Townsend et al [ 56 ], which uses the estimated substitution rates of individual molecular characters to estimate the power of a set of molecular sequences for resolving a four-taxon tree with equal subtending branch lengths. This result, applied to the Poisson model of molecular evolution, was subsequently generalized by Su et al [ 57 ] to apply to all standard symmetric molecular evolutionary models of nucleotide substitution up to and including the General Time Reversible model (GTR [ 58 , 59 ]). Herein we further generalize the signal and noise analysis by relaxing the assumption of equal subtending branch lengths for the four-taxon tree.…”
Section: Introductionmentioning
confidence: 99%
“…The Markov chain of a nucleotide character under the GTR model is commonly mathematically modeled by a four-by-four substitution rate matrix Q ( λ ), whose element q ij gives the instantaneous rate at which the nucleotide character changes from nucleotide i to nucleotide j , where j ≠ i, and i, j = T, C, A, or G ( c.f. Equation 1 in [ 57 ]). The average substitution rate of the character, λ , can be calculated as …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations